Using semiotic resources to teach and assess scientific concepts in a bilingual Namibian primary school: A socio-cultural discourse analysis - Set, Beatha Ndahafa (School of Education, 2022)
The Namibian school system subscribes to a separatist language policy and ideology that advocates the use of monolingual English as Medium of instruction (MO1) as well as conducting all written assessments from Grade 4 and beyond in English. Despite Namibia being a multilingual country, the Namibian monolingualist Language in Education Policy (LiEP) makes no provision to accommodate multilingual practices and to fulfill the linguistic needs of learners from linguistically diverse backgrounds, who lack proficiency in English. The language separatist ideologies sanctioned in the Namibian LiEP as well as in science written assessments need further consideration in order to embrace language as an open system that is fluid, evolving, and hybrid. Given the complexities of the language policy and pedagogical challenges of language of instruction choices in the Namibian classrooms, I wanted to investigate how primary school Science teachers and learners meet the demand of the Namibian curriculum of Learner Centered Education (LCE) and the ideologies of monolingualism advocated in the Namibian Language in Education Policy. I undertook a small-scale, ethnographically informed case study approach to examine the nature of discourse employed by a Grade 4 teacher and his learners (aged 10- 12) in a bilingual Namibian classroom as they engaged in science classroom discourse, exploring how these specific discourses support or constrain learners' opportunities to construct scientific meaning. I combined various theoretical resources from a sociocultural approach to language as social practice, Bakhtinian heteroglossia and dialogism, neo-Vygotskian ideas of what constitutes the learning of scientific concepts, together with the recent theorising of dynamic bi/multilingualism to understand this phenomenon in depth. The data include video and audio recordings of lessons, field notes, learning materials, policy document, photographs , interviews, written work (drawing and writing) as well learners' written science assessments. The data was analysed through sociocultural discourse and multimodal analytical methods. This study's findings suggest that in contrast with dialogic practices, monologic practices were dominant, as evidenced by the constrained Initiation Response Feedback (IRF) discourse structure. This suggests that English monolingual policy places constraints on bilingual learners to use their multiple linguistic recourses flexibly and thereby silenced their voices in the classroom. This implies that the struggle to break away from rote leaning towards conceptual understanding through exploratory talk remains elusive for the Namibian bilingual learners. Therefore, I suggest that one cannot argue for dialogism or for conceptually rigorous instruction in scientific concepts if the learners cannot understand the language of instruction. The discussion of dialogism and multimodality as a sole vehicle for raising the quality of science teaching should be further complimented with a consideration of deliberate use of multilingual and multimodal meaning making which enables teachers to value their learners' linguistic resources that they brought to school to enable effective science teaching and learning. The findings of this study revealed how the affordances of multiple linguistic resources and modes have positive effects for emergent bilingual learners to gain nuanced understanding of the scientific knowledge, regardless of their limited proficiency in English. I will therefore argue that the prevailing monoglossic orientations to the current Namibian education system is a major contributing factor preventing Namibia to realise its' educational goals of access, quality, equity, and social justice. There is a need to support learners from linguistically diverse backgrounds through a deliberate inclusive language policy that harnesses their multilingualism and their cultural identity to enhance equal education access to all Namibian children. Clear direction is warranted on how teachers can publicly acknowledge and sustain their learners' linguistic and cultural resources in science written assessments.